Follow the River: City Regeneration in Tension as Works of Water - Polina Golovátina-Mora (Changing Societies & Personalities, 2022)
The article looks at some examples of the urban regeneration strategies and initiatives in Medellín, Colombia. Being part of the process of regeneration of the country after the decades of the armed conflict the initiatives transform the city at least by creating the discourse that facilitates the social change in the city. The ontological proposal of feminist more-than-humanism focusing on materiality of water, particularly its rhizomatic connectivity, allows rethinking the concept of the city and its regeneration as generation of the inclusive space that provides habitat and life for anyone who wants to live in, around, through, and with the city. The revised initiatives are symbolically divided into two groups: water plans of connection-fragmentation policy and traces of water—mostly grassroots connectivity in response to the dominating power structures. They are not uniform groups and are the products/processes of tension between opposite tendencies. Creative tension is works of water. Water looks at limitations as at the opportunity to create the new. Its regeneration is not re- but generation of the inclusive habitat that provides life for anyone who wants to live in, around, through, and with the city.